The dynamics of redistribution, inequality and growth across China's regions - Xiaoliang Yang; Lucy Barros; Kent Matthews; David Meenagh (Cardiff University, Cardiff Business School, 2023)
China's fast growth has been accompanied by rising regional inequality, triggering debate over a policy trade-off between aggregate growth and equity. We set out a three-region model of China in which local government behavior affects local TFP dynamics, and regional inequality itself generates more regional productivity divergence. These dynamics can also be affected by central government transfers to regions. Two kinds of fiscal transfers are investigated: equalization transfers and the tax rebate. We estimate and test the model by indirect inference, and explore transfer policy reforms. The results suggest that transfer policies pursued since 1994 have prevented a 15% rise in regional inequality, though at an 8% cost to aggregate GDP.
Keywords: E60; H30; H70; O40; 330; Regional inequality; China; Fiscal decentralization; Redistribution; Local Government; Growth